Analisis Nilai Kehidupan Dalam Cerpen “Gubrak” Karya Seno Gumira Ajidarma Dengan Pendekatan Semiotika - Asni Asmawati; Isma Khoiriyah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Literary works are literary results, creations in the form of poems, prose, and plays (drama). Literary works are born as embodiments or depictions of life poured through the medium of writing. Therefore, it is closely related between literature and life. Through literature, the reader can express the meaning behind the work of the author. This research would examine a short story entitled